THE USE OF CEMARA UDANG (Casuarina equisetifolia) FOR AGRICULTURAL PURPOSES IN THE SOUTHERN COAST OF YOGYAKARTA - Atus Syahbudin; Dwi Tyaningsih Adriyanti; Anisa Handayani; Hu Bai; Katsuya Osozawa; Ikuo Ninomiya (UPT Penerbitan Universitas Jember, 2012)
An exploration along the Southern Coast of Yogyakarta and deep interview with276 respondents in the Southern Coast of Kulon Progo and Gunungkidul Regencies hadbeen conducting during January 2010 and February-May 2012. Respondents recognizedthat before the establishment of Casuarina equisetifolia they faced problems like strongwind in the agricultural land (81.6%), uncultivated land near the coast (20.3%), agriculturecrops die because of salt water (17%), and others (11.3%). During 16 years theestablishment of C. equisetifolia has been creating vegetative wind barrier due to Attims'tree architecture model. C. equisetifolia reduces the use of dried coconut leaf/blarak(29.3%) and objectifies green coastal landscape, which makes farmer, fisherman,inhabitant, visitor and merchant become pleasant. In addition, C. equisetifolia providesbenefits as shady tree for agricultural nursery (10.9%), mulch (10.4%), fertilizer (3.3%),and many kinds (49.4%). Reduction in the use of blarak, mulch and purchased fertilizerwill increase farmer’s income because the cost of labor, fertilizer and mulch decrease.